1992
DOI: 10.1017/s0004972700011862
|View full text |Cite
|
Sign up to set email alerts
|

Representations of finite groups and Cuntz-Krieger algebras

Abstract: We investigate the structure of the C *-algebras O p constructed by Doplicher and Roberts from the intertwining operators between the tensor powers of a representation p of a compact group. We show that each Doplicher-Roberts algebra is isomorphic to a corner in the Cuntz-Krieger algebra OA of a {0,1}-matrix A -A p associated to p. When the group is finite, we can then use Cuntz's calculation of the if-theory of OA to compute K.(O P ).Doplicher and Roberts have recently developed a duality theory for compact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 4 publications
2
53
0
Order By: Relevance
“…In [10] , it was shown that 0 P was isomorphic to a corner in a C * -algebra generated by an infinite Cuntz-Krieger family; now we know by Theorem 1 that this Cuntz-Krieger algebra GA P is simple, we have K # (G p ) = K * (@AP) , and we can use Theorem 3 to compute K * (Gp) . In fact, we can do better: we can identify Z°° with the representation ring $Z(G), and K* (G p The following definitions and results are extensions of those given in [5, p.253] , where it is claimed that their results for finite matrices carry over to the infinite case.…”
Section: Theorem 2 8 Let B Be Unital C * -Algebra and $ A Strongly Comentioning
confidence: 95%
See 2 more Smart Citations
“…In [10] , it was shown that 0 P was isomorphic to a corner in a C * -algebra generated by an infinite Cuntz-Krieger family; now we know by Theorem 1 that this Cuntz-Krieger algebra GA P is simple, we have K # (G p ) = K * (@AP) , and we can use Theorem 3 to compute K * (Gp) . In fact, we can do better: we can identify Z°° with the representation ring $Z(G), and K* (G p The following definitions and results are extensions of those given in [5, p.253] , where it is claimed that their results for finite matrices carry over to the infinite case.…”
Section: Theorem 2 8 Let B Be Unital C * -Algebra and $ A Strongly Comentioning
confidence: 95%
“…These C* -algebras are built from spaces of intertwiners between tensor powers of a given faithful representation p: G-> SU(ffl) , where G is a compact group and l<dim($C) <°o i We refer to [10] for further details of their construction. Decomposing the tensor powers of p into irreducible components yields a countable 0-1 matrix A p, which may be shown to be irreducible and row finite.…”
Section: Doplicher-roberts Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…For finite graphs, these are precisely the Cuntz-Krieger algebras O A : given E, take A to be the edge matrix A E defined by A E (e, f ) = 1 if r(e) = s(f ), 0 if r(e) = s(f ); (1.2) conversely, given an I × I matrix A, form the graph E A with vertex set I and incidence matrix A, and then C * (E A ) is isomorphic to O A in a slightly nonobvious way (see [9,Theorem 3] or [13,Proposition 4.1]). This correspondence carries over to locally finite graphs (graphs in which vertices receive and emit finitely many edges), and the classical uniqueness and simplicity theorems for Cuntz-Krieger algebras have elegant extensions to these graph algebras [11,12].…”
mentioning
confidence: 99%
“…We can then use the results of [7] to obtain uniqueness and simplicity theorems for C * (E). It is not clear whether the reverse passage from Cuntz-Krieger algebras to graph algebras is always possible for graphs which are not locally finite: the obvious analogue of the isomorphism of O A onto C * (E A ) given in [9] and [13] would involve infinite sums of the sort we have to avoid in abstract C * -algebras. We shall begin by giving precise definitions and stating our main results.…”
mentioning
confidence: 99%